Not the Master of Your Volitional Mind? The Roles of the Right Medial Prefrontal Cortex and Personality Traits in Unconscious Introjections Versus Self-Chosen Goals - Quirin, Markus; Kerber, André; Küstermann, Ekkehard; Radtke, Elise L.; Kazén, Miguel; Konrad, Carsten; Baumann, Nicola; Ryan, Richard M.; Ennis, Michael; Kuhl, Julius (Frontiers in Psychology, 2022)
Humans are unconditionally confronted with social expectations and norms, up to a degree that they, or some of them, have a hard time recognizing what they actually want. This renders them susceptible for introjection, that is, to unwittingly or “unconsciously” mistake social expectations for self-chosen goals. Such introjections compromise an individual’s autonomy and mental health and have been shown to be more prevalent in individuals with rumination tendencies and low emotional self-awareness. In this brain imaging study, we draw on a source memory task and found that introjections, as indicated by imposed tasks that are falsely recognized as self-chosen, involved the bilateral medial prefrontal cortex (MPFC) and the dorsal anterior cingulate cortex (ACC). Notably, reduced right MPFC activation within this condition correlated with trait scores of ruminations and reduced emotional self-awareness, but also introversion. Moreover, correct recognition of tasks as self-chosen involved the right MPFC. Accordingly, the right MPFC may play a role in supporting the maintenance of psychological autonomy and counteract introjection, which individuals with certain personality traits seem to be prone to. This research has significant implications for the study of mechanisms underlying autonomous motivation, goal and norm internalization, decision-making, persuasion, education, and clinical conditions such as depression and burnout.